Aplicação de controlador preditivo baseado em modelo (MPC) para sistema de geração distribuída constituído por inversor trifásico a quatro braços - Pinto, Lázaro Rubens Araújo (2017)
This work proposes an analysis of the closed-loop operation of a distributed generation system connected to a three-phase four-wire AC power system by a three-phase four-leg inverter. The modulation strategy adopted for this inverter is determined by the Model Predictive Control (MPC) method. Reasons for the use of this topology and the control method are discussed. The chosen structure for the MPC predictive control aims to supply of active and reactive power by the inverter in order to maximize the power factor measured by the four-wire AC source (Y-n). Four possible cases of operation are reported for the analysis of the proposal in the three-phase four-leg inverter and other two cases for a three-phase full-bridge inverter (3F) for comparison purposes. Based on the monitoring of the active powers involved and the other variables of interest, it was possible to exemplify the achievement of the proposed objectives and validate the adopted method, at least under modeling and software simulation level.